Performance of Popular Hevea Clones Under Tea Intercropping System in Tripura Climatic Condition - DEY, S.K.; PAL, T.K.; NAZEER, M.A.; JACOB, J. (Indian Journal of Hill Farming, 2015)
A study was carried out in four popular clones of Hevea brasiliensis to evaluate clonal performance under tea inter cropping system in Tripura (North East India). Rubber was planted in four row bands aligned in the North West – South West direction. Tea was planted as an intercrop between the rubber bands and tea comprised of 25% of the land area. Among the clones, RRIM 600 showed highest yield (1573 kg/ha) followed by PB 235, RRII 105 and GT 1 during initial four years of tapping. Rubber yield was low during summer months and an increasing trend of yield was observed with a maximum in November. In case of tea, maximum green tea leaf yield was observed in the month of June and annual average over four years of green tea leaf yield was 887 kg/ha. In this study, no adverse affect was noticed due to inter cropping of tea in rubber. However, soil nutrition status was increased over the years of cultivation. Since both the crops are the long term crop, the effect needs to be studied for a longer period of time.